PENGARUH TEKNIK PEMBELAJARAN THINK TALK WRITE (TTW) BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS FABEL - Wahyuni, Nendi Dwi; Thahar, Harris Effendi (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this writing is to research the influence of TTWâ€™s learning by using picture in series as the media towards class VII of SMP Negeri 2 2X11 Enam Lingkungâ€™s studentsâ€™ skill on writing fable. The data of this research are the studentsâ€™ scores of writing fables. It is collected by doing the test of writing fable toward the sample before and after using TTWâ€™s technique by using picture in series. The result of this technique is using T-test formula. The result of this research showing 1) the writing skill of fable before and after using TTWâ€™s technique of picture in series are in â€œLebih dari Cukupâ€ (LdC) qualification; 2) the writing skill of fable before and after using TTWâ€™s technique of picture in series are in the â€œBaik Sekaliâ€ (BS) qualification and 3) as the result of using T-test formula showing that the writing skill of fable before and after using TTWâ€™s technique of picture in series giving very good influence towards the studentsâ€™ skill of writing fable text in class VII of SMP Negeri 2 2X11 Enam Lingkung.Â Kata kunci:Â Pengaruh, TTW Berbantuan Media Gambar Berseri, Keterampilan Menulis Teks FabelÂ